Nieetyczne postawy podatników jako zagrożenie bezpieczeństwa finansowego państwa - Pasternak-Malicka, Monika (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article describes the ethical aspect of the taxpayers’ attitudes and summariesresearch indicating a deficit of ethical behavior among households and businessentities. Linear regression method was used to show the statistical relationshipbetween the level of the shadow economy and tax revenues in Poland. The purposeof this article is to present the essence of Poles’ morality on taxation resultingfrom the loss of civil instinct and ethical behavior in the context of their impacton the financial security of the state.